2013
DOI: 10.1016/j.febslet.2013.03.023
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐155 is a novel suppressor of ovarian cancer‐initiating cells that targets CLDN1

Abstract: a b s t r a c tPreviou s cDNA microarrays indicated that CLDN1 (claudin-1) is an important gene for ovarian cancer-init iating cell (OCIC) invasion and adhesion. Here, we show that the downregulation of miR-155 in OCICs correlates with CLDN1 overexpression and the suppression of OCIC invasion. Luciferase assay s indicate that miR-155 targets CLDN1 mRNA on the 3 0 UTR. CLDN1 mRNA and claudin-1 protein expressi on were significantly decreased in miR-155-OCICs. Proliferation assays and Transwell migration assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 23 publications
1
75
0
1
Order By: Relevance
“…CLDN1, one of the major components of TJs, is among the direct targets of miR‐155 42, 43. While CLDN5 is highly expressed in the brain endothelium, CLDN1 expression in cerebral capillaries is low and was only confirmed to be present in human, rat, and sheep BBB 3, 30, 31.…”
Section: Discussionmentioning
confidence: 99%
“…CLDN1, one of the major components of TJs, is among the direct targets of miR‐155 42, 43. While CLDN5 is highly expressed in the brain endothelium, CLDN1 expression in cerebral capillaries is low and was only confirmed to be present in human, rat, and sheep BBB 3, 30, 31.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results in luciferase reporter assay, the miR-30c was related to the invasion of NSCLC by regulating MTA1. MiRNAs can regulate the target gene expression by binding its 3′-UTR [26,27,28]. However, the mechanism of miR-30c requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that miR-155 is up-regulated by the transforming growth factor β (TGF-β) pathway, which plays an important role in TGF-β-induced EMT in breast cancer cells [25]. In addition, a recent study showed that miR-155 overexpression inhibits ovarian cancer-initiating cell proliferation and invasion [26]. However, the role of miR-155 in HCC cells during the EMT and acquisition of the cancer stem cell phenotype is not fully understood.…”
Section: Introductionmentioning
confidence: 99%